2020
DOI: 10.30919/esmm5f711
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Conductive Properties of Smart Cementitious Composites with Conductive Rubber Crumbs

Abstract: Massive waste rubber products become very challenging because the disposal generates negative impacts on the ecological environments. The effect of conductive rubber crumbs replacing the fine aggregate on the physical, mechanical properties and electrical characteristics of cement composites were investigated in this study. The results show that the flowability of cement mortar increased when the rubber crumbs replacement rate lower than 10%, but decreased when the substitution rate higher than 10%. The compre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Another approach suggested that the main contribution to conduction is given by water diffusion through the porous network resulting in ion conductivity (5,15), such as with the increase of the conductive filler content, the electrical conductivity increases gradually because the conductive solutions promote the elongation and connection of the conductive passages (16).…”
Section: Figure 3 Electrical Conductivity Of Concrete Versus Volume F...mentioning
confidence: 99%
“…Another approach suggested that the main contribution to conduction is given by water diffusion through the porous network resulting in ion conductivity (5,15), such as with the increase of the conductive filler content, the electrical conductivity increases gradually because the conductive solutions promote the elongation and connection of the conductive passages (16).…”
Section: Figure 3 Electrical Conductivity Of Concrete Versus Volume F...mentioning
confidence: 99%
“…Polymer materials are widely used in many important fields such as aerospace, [235] electronics, [236,237] pharmaceutical carriers, [238,239] chemical industry [240] and other important fields [241] because of these materials have the advantages of light weight, high dispersion, easy modification, and corrosion resistance. [242][243][244] The composite materials prepared with boron nitride as filler can combine the advantages of boron nitride and polymer, so as to obtain the composite materials with excellent comprehensive properties.…”
Section: Polymer Composite Materialsmentioning
confidence: 99%
“…The recent trend of wearable electronics in research as well as industries shows that these devices hold a promising future. Polymer composites are extensively explored for various applications such as supercapacitors, 7 smart technologies, 8 and green tires 9 . Moreover, these studies are expected to evolve further with innovative integrity and seamless user experience.…”
Section: Introductionmentioning
confidence: 99%